Large is Beautiful – Progress of HelioFocus 500 m2 Dish. (May 2015) - Keck, T.; Balz, M.; Blumenthal, Y.
Abstract: System and component improvements and further development of the HelioFocus dish are described, which is the largest point-focusing concentrator worldwide. An overview of the innovative system is given and enhancements of concentrator, turn table, receiver and heat transfer are shown. Testing of new components and assemblies was conducted at the prototype dish in Israel. A demonstration plant with eight units was erected in China and shall be extended in further steps. Another demonstration plant in Israel is under construction, and several more projects are being developed.